Beauveria bassiana biogenic nanoparticles for the control of Noctuidae pests - Guilger-Casagrande, Mariana [UNESP]; Migliorini, Bianca Bertolini; Germano-Costa, Tais; Bilesky-José, Natália; Harada, Liliam Katsue [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; Gonçalves, Kelly Cristina [UNESP]; Polanczyk, Ricardo Antonio [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Lima, Renata (Wiley, 2024)
BACKGROUND: Biogenic metallic and oxide metal nanoparticles have potential as alternatives for several current problems in agriculture, such as the control of caterpillars which cause huge losses in the production of important crops. In the present study, capped and uncapped silver, iron oxide and titanium dioxide nanoparticles were synthesized from the filtrate of Beauveria bassiana and evaluated in regard to physico-chemical characteristics, capping composition, cytotoxicity, genotoxicity and biological activity on Helicoverpa armigera and Spodoptera frugiperda caterpillars. RESULTS: A difference in the physico-chemical parameters of the capped and uncapped nanoparticles was observed, with larger aggregation and lower stability of the uncapped. In regard to the study of the capping, the presence of functional groups of biomolecules as well as the activity of B. bassiana hydrolytic enzymes were observed. Cytotoxic effects on the tested cell lines were not observed and DNA damage levels increased with more intense effects of the uncapped nanoparticles. In regard to the biological activity against Noctuidae pests, the uncapped and capped iron oxide, and uncapped titanium dioxide nanoparticles occasioned higher mortality (76%, 60% and 51%, respectively) but no differences in LC50 were recorded. Moreover, sublethal effects were reported on Helicoverpa armigera whereas Spodoptera frugiperda showed low susceptibility to the nanoparticles. CONCLUSION: The results demonstrate that biogenic metallic and oxide metal nanoparticles might show promising effects for the control of caterpillars which cause damage on important agricultural crops. Further investigations are necessary to understand the mechanisms of action and optimize the biological activity of these new nanomaterials. © 2023 Society of Chemical Industry.
Keywords: green synthesis of nanoparticles; Helicoverpa armigera; pest control; Spodoptera frugiperda; sustainable agriculture